Computational fluid dynamics simulations to optimize the filling of an underground mine cavity with fly ash. Issue 5 (3rd September 2017) - Song, Changheon; Kim, Daeji; Kang, Hoon; Cho, Min-Gi; Park, Jin-Young; Cho, Jung-Woo; Lee, Sang-Eun
Abstract: Subsidence caused by the underground spaces of abandoned mines is a potential danger to life and property. This study focuses on optimizing the filling of these cavities at a site in Korea to prevent subsidence and to reuse abandoned mine. Fly ash produced from thermoelectric power plants might be profitably used to fill the abandoned workings. Computational fluid dynamics (CFD) is used here to simulate fly ash injection into mine cavities by a volume-of-fluid method. The numerical experiments are run after the establishment of three input parameters, which are used to optimize two output parameters. This series of CFD simulations investigates the effects of filling with respect to the operation factors of the filling method. The filling operation is then optimized with regard to efficiency and equipment cost. A low injection point with drilling connection of vertical shafts gives the most efficient filling of underground mine cavities.